APLIKASI LIMBAH CAIR CPO (Crude Palm Oil) DAN ABU JANJANG KELAPA SAWIT PADA TANAMAN CABE RAWIT - Hendrik Bangun; Hasan Basri Jumin; Siti Zahrah (UIR Press, 2014)
This research aims to examine the effect of CPO (Crude Plam Oil) sludge and ash of palm oil addition on growth and chili. The research was carried out at the experimental farm Faculty of Agriculture Riau Islamic University from September 2012 to January 2013. The experimental with Completely Randomized Design for Factorial 4 x 4 were used. The first factor was various doses CPO sludge addition, consisting of four levels, that is 0, 100, 200, 300 cc each plant and second factor was based on various ash doses of palm oil, consisting of four levels, namely 0, 100, 200, 300 g each plant. The result of research indicates that the interactian effect of treatment was significant to height of plant and chili yield. The best treatment was addition of CPO sludge 300 cc/plant and ash of palm oil 300 g/plant with height of plant (53,58 cm) and chili yield (670 g/plant).